Effectiveness of exercise interventions in animal models of multiple sclerosis - Parnow, Abdolhossein; Hafedh, Muthanna; Tsunoda, Ikuo; Patel, Darpan I.; Baker, Julien S.; Saeidi, Ayoub; Bagchi, Sovan; Sengupta, Pallav; Dutta, Sulagna; Łuszczki, Edyta; Stolarczyk, Artur; Oleksy, Łukasz; et al. (Frontiers in Medicine, 2023)
Multiple sclerosis (MS) is a condition associated with impaired immune system severely affecting the spinal cord and brain, marked by progressive inflammatory demyelination. Patients with MS may benefit from exercise training as a suggested course of treatment. The most often used animal in studies on MS are experimental autoimmune/allergic encephalomyelitis (EAE) models. The present review intends to concisely discuss the interventions using EAE models to understand the effectiveness of exercise as treatment for MS patients and thereby provide clear perspective for future research and MS management. For the present literature review, relevant published articles on EAE animal model that reported the impacts of exercise on MS, were extracted from various databases. Existing literature support that exercise regimen can reduce the severity of some of the clinical manifestations of EAE, including neurological signs, motor function, pain, and cognitive deficits. Further results demonstrate the mechanisms of EAE suppression with information relating to the immune system, demyelination, regeneration, and exercise in EAE. The role for neurotrophic factors has been also been investigated. Analysing the existing reports, the article infers that EAE is a suitable a beneficial animal model that can help researchers develop further understanding and treatments for MS, and also. Besides, findings from previous animal studies supports the contention that exercise assists in ameliorating MS progression.